Diversity of the board of directors of psi-20 listed companies - Santos Loureiro da Silva, Amaro Jorge (2021)
At a time when the economies sustaining the financial and business system are shaken by serious systemic crises and financial fraud, political pressure is mounting to scrutinise the diversity of the board of directors (BoD) of companies to understand whether, in fact, a heterogeneous group can produce strategic and tactical decisions best suited to the future of the company. In addition, questions arise regarding the role of women in the BoD, contributing to the idea that they may increase management prospects. In this context, this study aims to analyse and characterise the diversity of the BoD of companies listed on the PSI-20 in 2019. Specifically, it intends to analyse the diversity in the light of the formal mechanisms of corporate governance of an internal nature under four dimensions: (i) gender diversity; (ii) age diversity; (iii) cultural/ethnic diversity; and (iv) diversity in structure (independence and duality of CEO/Chairman functions). To achieve this objective, the study was based on a collection of qualitative data based on the Reports and Accounts for the year 2019, which, using Microsoft Excel for statistical processing, made it possible to analyse the profile of 215 directors. It can be concluded that the BoD of the companies included on thePSI-20 is composed mostly of male members, although there is an increasing tendency towards the presence of the female gender. In addition, the average age of women is lower than that of men. Regarding cultural/ethnic diversity, there is a higher representation of outsiders in the BoD of non-family companies. Regarding the structure of the board, the existence of an appropriate relationship of proportionality between executive and non-executive directors is highlighted. The same is not true for independentdirectors. On the other hand, 50% of the companies have a separation between the Chairman and the CEO, which provides an incentive for a more transparent and balanced governance model, providing a better balance of power.